Exposing an “Intangible” Cognitive Skill Among Collegiate Football Players: III. Enhanced Reaction Control to Motion - Wylie, Scott A.; Ally, Brandon A.; van Wouwe, Nelleke C.; Neimat, Joseph S.; van den Wildenberg, Wery P. M.; Bashore, Theodore R. (Frontiers in Sports and Active Living, 2019)
Football is played in a dynamic, often unpredictable, visual environment in which players are challenged to process and respond with speed and flexibility to critical incoming stimulus events. To meet this challenge, we hypothesize that football players possess, in conjunction with their extraordinary physical skills, exceptionally proficient executive cognitive control systems that optimize response execution. It is particularly important for these systems to be proficient at coordinating directional reaction and counter-reaction decisions to the very rapid lateral movements routinely made by their opponents during a game. Despite the importance of this executive skill to successful on-field performance, it has not been studied in football players. To fill this void, we compared the performances of Division I college football players (n=525) and their non-athlete age counterparts (n=40) in a motion-based S(timulus)-R(esponse) compatibility task that assessed their proficiency at executing either compatible (in the same direction) or incompatible (in the opposite direction) lateralized movements to a target’s lateral motion. We added an element of decision uncertainty and complexity by giving them either sufficient or insufficient time to preload the response decision rule (i.e., compatible versus incompatible) prior to the target setting in motion. Overall, football players were significantly faster than non-athlete controls in their choice reactions to a target’s lateral motion. The reactions of all participants slowed when issuing incompatible counter-reactions to a target’s lateral motion. For football players, this cost was reduced substantially compared to controls when given insufficient time to preload the decision rule, indicating that they exerted superior executive control over their reactions and counter-reactions when faced with decision uncertainty at the onset of stimulus motion. We consider putative sources of their advantage in reacting to a target’s lateral motion and discuss how these findings advance the hypothesis that football players utilize highly-proficient executive control systems to overcome processing conflicts during motor performance.